(untitled) (Altre Modernità, 2018)
The Vasconcelos and Zambrano attempt to reconcile life and reason, Wisdom and Philosophy, is particularly affected by the influence of the aesthetic and ‘musical’ component of Pythagoreanism. This, that would cross the history of philosophy as an heterodox current, intends to reassert itself, as much in Vasconcelos aesthetic thought as in Zambrano’s Poetic Reason, against the constraints of rationalism, its formal rigidity and its dogmatism. With this objective, their reflection about the complex articulation and declination of the history of philosophy in literary genres, as places of its intimate drama, flows in the analysis of two specific and, in some respects, similar forms of literature: the symphony (Vasconcelos) and the confession (Zambrano). The latter is nothing new in the literary scene but, recognized as true of Western thinking method, is proposed as a conditio sine qua non of its authentic rebirth. Symphony and confession, which in their analogical and musical process would realize the ancient Pythagorean inspiration, insist on the need to invalidate that world devoid of subject, to reveal the immobilism and the absolutism of the concept and to rethink the tragedy, as a genre and in its historical manifestations, to forestall its ending. They share, therefore, the same purpose: the fulfillment of an ‘ethical Hystory’.